Functional immune monitoring in severely injured patients—A pilot study. (3rd November 2019) - Halbgebauer, Rebecca; Kellermann, Stephanie; Schäfer, Fabian; Weckbach, Sebastian; Weiss, Manfred; Barth, Eberhard; Bracht, Hendrik; Kalbitz, Miriam; Gebhard, Florian; Huber‐Lang, Markus S.; Perl, Mario
Abstract: After severe trauma, the resulting excessive inflammatory response is countered by compensatory anti‐inflammatory mechanisms. The systemic inflammatory response to trauma enhanced by inappropriately timed surgical second hits may be detrimental for the patient. On the other hand, overwhelming anti‐inflammatory mechanisms may put patients at increased risk from secondary local and systemic infections. The ensuing sepsis and organ dysfunction due to immune dysregulation remain the leading causes of death after injury. To date, there are no clinically applicable techniques to monitor the pro‐/anti‐inflammatory immune status of the patients and the remaining ability to react to microbial stimuli. Therefore, in the present study, we used a highly standardized and easy‐to‐use system to draw peripheral whole blood from polytraumatized patients (ISS ≥ 32, n = 7) and to challenge it with bacterial lipopolysaccharide. Secreted cytokines were compared with those in samples from healthy volunteers. We observed a significant decrease in the release of monocyte‐derived mediators. Surprisingly, we detected stable or even increased concentrations of cytokines related to T cell maturation and function. For clinical practicability, we reduced the incubation time before supernatants were collected. Even after an abbreviated stimulation period, a stable release of almost all analysed parameters in patient blood could be detected. In conclusion, the data are indicative of a clinically well‐applicable approach to monitor the immune status in severely injured patients in a short time. This may be used to optimize the timing of necessary surgical interventions to avoid a boost of proinflammation and reduce risk of secondary infections.